In search of financial stability - the case of shadow banking - Lucius, Otto (Managerial Economics, 2014)
Financial stability seems to be an important buzzword these days. This paper discusses the threats to financial stability that might arise from shadow banking. In order to properly discuss the problems, shadow banking is defined. Then, which measures to take to remedy this situation will be discussed.